2018
DOI: 10.2147/cmar.s172687
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy during cytoreductive surgery in epithelial ovarian cancer

Abstract: BackgroundThe aim of the study was to analyze the underlying causes and application of splenectomy in patients with epithelial ovarian cancer (EOC) and assess its effect on the surgical satisfaction and prognosis of these patients.Materials and methodsClinical data of patients with ovarian epithelial cancer treated with cytoreductive surgery were collected from 2000 to 2015 at Peking Union Medical College Hospital.ResultsA total of 2,882 patients underwent ovarian cancer cytoreductive surgery at Peking Union M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 45 publications
3
27
1
Order By: Relevance
“…Previous studies have shown conflicting results regarding splenectomy and the survival of patients with malignancies. [18][19][20][21] The spleen usually…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown conflicting results regarding splenectomy and the survival of patients with malignancies. [18][19][20][21] The spleen usually…”
Section: Discussionmentioning
confidence: 99%
“…The main indication of splenectomy is macroscopic invasion, much less accidental intraoperative trauma. Splenectomy improves overall survival, so it is recommended to be performed in all patients with local invasion, both in primary and secondary surgical cededuction [35].…”
Section: • Interval Citoreductionmentioning
confidence: 99%
“…It is well accepted that optimal cytoreduction improves survival in ovarian cancer patients [3,4] . In some circumstances, removal of the spleen as part of upper abdominal surgery is required to achieve complete resection [5,6] .…”
Section: Introductionmentioning
confidence: 99%